Islamic Spiritual Deconstruction: Kanjeng Ratu Kidul Myth in Kiai Ibnu Hajar’s View - Suwito, S.; Ulyan, Mohammad; Novianti, Ida; Muflihah, M. (LPPM IAIN Kudus, 2020)
This article aims to study and analyze the Islamic spiritual sides of the deconstruction in Kanjeng Ratu Kidul belief from the perspective of Kiai Ibnu Hajar. Kanjeng Ratu Kidul is a very popular myth among people in the southern part of Java Island. Most of them hold annual ceremonies as a way to express their request for having the blessing and being avoided from disasters. The data of this research were collected through in-depth interviews and participatory observations. Derrida’s deconstruction theory was applied to analyze the spirituality aspects. There are three deconstruction processes: (1) logocentric identification; (2) internal contradiction return; (3) difference or building new construction. This research found that Kiai Ibnu Hajar’s deconstruction spirituality was performed in three stages: (1) visual identification stage, which is done through eliciting the discourse of Kanjeng Ratu Kidul by her pictures or photos; (2) returning stage, which is done through mind-verbal activities, i.e. by understanding the nature and existence of human being through religious teachings and informal chats; (3) building new concept, which is actualized through the use of new terms among the members of Jamaah Aolia Panggang Mosque.